Current Evidence Related to Intermittent Catheterization: A Scoping Review. Issue 2 (March 2020) - Engberg, Sandra; Clapper, Jynae; McNichol, Laurie; Thompson, Donna; Welch, Valre W.; Gray, Mikel
Abstract : PURPOSE: The purpose was to summarize evidence related to adherence to intermittent catheterization (IC), complication rates, satisfaction with IC, and its effect on health-related quality of life. PROBLEM: Intermittent catheterization is frequently used to manage lower urinary tract dysfunctions including urinary retention and urinary incontinence, but research suggests that care for patients using IC may not always be based on evidence. METHODS: Scoping review. SEARCH STRATEGY: We searched the PubMed, EMBASE, CINAHL databases, and the Cochrane Database for Systematic Reviews to identify studies published between January 2009 and March 2019. Seventy studies met inclusion criteria and were evaluated for adherence, complication rates, satisfaction, and health-related quality in adults and children using IC for bladder management. FINDINGS: Recent research was variable in both quantity and quality. The evidence suggests that (1) most patients can successfully master IC and that functional status is likely the most important predictor of success; (2) adherence to IC probably decreases over time; (3) urinary tract infections (UTIs) are the most common complication of IC and that prophylactic antibiotic therapy may reduce the risk of recurrent UTIs; (4) urinary incontinence is also a common complication; and (5) other complications such as urethral strictures, bladder stones, hematuria, and urethral false passage do occur but are less prevalent than UTIs and incontinence between catheterizations. Our review also revealed multiple gaps in the evidence to support care for patients using IC. CONCLUSIONS: Research priorities include a need for prospective studies of the epidemiology and risk factors for IC-related complications, along with intervention studies to determine how to improve outcomes for patients using IC to manage bladder function. Abstract : The CE test for this article is available online only at the journal website, jwocnonline.com, and the test can be taken online at NursingCenter.com.